Interaksi edukatif guru kunjung sebagai strategi alternatif meningkatkan motivasi belajar dalam pembelajaran masa pandemi COVID-19 - Meilisa Novariana (Indonesian Journal of Educational Development, 2021)
The government policy through the Ministry of Education and Culture related to the pandemic period is the adjustment of learning during the Covid-19 Virus pandemic, where the learning process in schools that was initially carried out direct learning must be replaced with an online (online) and offline (offline) system. One of the things that must be in the mind of an educator in implementing this distance learning is to humanize the relationship. This best practice aims to describe the effectiveness of "ge-je" (Guru kunJung/teacher’s visit) educational interactions as an alternative strategy to increase learning motivation in implementing distance learning in order to humanize the relationship between teachers and students through providing learning motivation to conditions for students who have special obstacles such as limited funds to buy quotas, lack of understanding of the material, and those involved in economic activities at home. This research uses qualitative methods, and for concrete data collection the authors carry out several data collection techniques, namely observation, interviews, and documentation. The subjects of this research were students of class IX-C at SMP Negeri 20 Malang. The result obtained is the importance of conducting an early diagnosis in the implementation of distance learning. Early diagnosis really needs to be done to get a information of student’s motivation and learning styles. In addition, the selection of the right approach, strategy and learning method, and the platform chosen must be adapted to the real situation of the area. In relatively safe areas, the implementation of the educational interaction strategy "ge-je" (Guru kunJung/teacher’s visit) is appropriate for students who have special obstacles such as limited funds to buy quotas, lack of understanding of the material, and those involved in economic activities at home. Kebijakan pemerintah melalui Kementerian Pendidikan dan Kebudayaan terkait dengan masa pandemi adalah penyesuaian pembelajaran di masa pandemi Virus Covid-19, di mana proses pembelajaran di sekolah yang semula dilakukan secara tatap muka harus diganti dengan sistem daring maupun luring. Salah satu hal yang harus ada pada pemikiran seorang pendidik dalam pelaksanaan pembelajaran jarak jauh ini adalah memanusiakan hubungan. Best practise ini bertujuan untuk memaparkan efektivitas interaksi edukatif “ge-je” (Guru kunJung) sebagai strategi alternatif meningkatkan motivasi belajar dalam pelaksanaan pembelajaran jarak jauh dalam rangka memanusiakan hubungan antara guru dan siswa melalui pemberian motivasi belajar pada kondisi pada siswa yang mempunyai hambatan khusus seperti keterbatasan dana untuk membeli kuota, pemahaman terhadap materi kurang, dan yang terlibat aktivitas ekonomi di rumah. Penelitian ini menggunakan metode kualitatif, dan untuk pengumpulan data yang konkret penulis melaksanakan beberapa teknik pengumpulan data, yakni pengamatan, wawancara, dan dokumentasi. Subjek penelitian adalah siswa kelas IX-C di SMP Negeri 20 Malang. Hasil yang diperoleh adalah pentingnya dilakukan diagnosa awal dalam pelaksanaan pembelajaran jarak jauh. Diagnosa awal sangat perlu dilakukan untuk memperoleh gambaran motivasi dan gaya belajar siswa. Selain itu pemilihan pendekatan, strategi dan metode pembelajaran yang tepat, serta platform yang dipilih harus disesuaikan dengan situasi nyata daerah tersebut. Pada daerah yang relatif sudah aman, penerapan strategi interaksi edukatif “ge-je” (Guru kunJung) tepat dilakukan pada siswa yang mempunyai hambatan khusus seperti keterbatasan dana untuk membeli kuota, pemahaman terhadap materi kurang, dan yang terlibat aktivitas ekonomi di rumah.